The real number x satisfying the equation x + 2 x − 1 + x − 2 x − 1 = 1 0 can be written as b a where a and b are positive coprime integers. Find a + b .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Indeed, that was the inspiration behind this problem.
As you can see from the other solutions, almost everyone claims that 4 x − 2 = 1 0 2 , which arises from the incorrect claim that x 2 − 2 x + 1 = x − 1 .
where did the x came from? the 1st and the last..
Squaring both sides gives x + 2 x − 1 + x − 2 x − 1 + 2 x 2 − 2 x + 1 = 1 0 0 which can be simplified to 2 x + 2 ( x − 1 ) 2 = 1 0 0 which can further be simplified to 4 x − 2 = 1 0 0 solving for x we get 2 5 1 , 51 + 2 = 53, our final answer.
You forgot that ( x − 1 ) 2 = ∣ x − 1 ∣ .
To get rid of the nested radicals, let's both sides of the equation. This gives us x + 2 x − 1 + x − 2 x − 1 + 2 x 2 − ( 2 x − 1 ) = 1 0 0 Cancelling out and factoring gives us 2 x + 2 ( x − 1 ) 2 = 1 0 0 2 x + 2 ( x − 1 ) = 1 0 0 2 x − 1 = 5 0 2 x = 5 1 x = 2 5 1 5 1 + 2 = 5 3
Let a=x, b= 2 x − 1
a + b + a − b =10
Square both sides
a+b+2 ( a + b ) ( a − b ) +a-b=100
Rearranging and divide by 2 gives
( a + b ) ( a − b ) =50-a
Squaring both sides gives :
a 2 - b 2 =2500-100a+ a 2
Substitute b 2 =2x-1
And a=x
a 2 -2a+1=2500-100a+ a 2
Rearranging gives:
98a=2499
a= 2 5 1
51+2=53
Faltu itne lambe jhamele mein fansa
\sqrt{x + \sqrt{2x - 1}} + \sqrt{x - \sqrt{2x - 1}} = 10 \Rightarrow (\sqrt{x + \sqrt{2x - 1}} + \sqrt{x - \sqrt{2x - 1}}) ^ 2 = 100 \Rightarrow 2x + 2 \times (\sqrt{x + \sqrt{2x - 1}} \times \sqrt{x - \sqrt{2x - 1}}) = 100 \Rightarrow 2x+ 2 \times ( x - 1) = 100 \Rightarrow 4x = 102 \Rightarrow x = \frac {51}{2} Therefore a + b = 51 + 2 = 53
x + 2 x − 1 + x − 2 x − 1 = 1 0 = > ( x + 2 x − 1 + x − 2 x − 1 ) 2 = 1 0 2 = > ( x + 2 x − 1 ) 2 + 2 ∗ x + 2 x − 1 ∗ x − 2 x − 1 + ( x − 2 x − 1 ) 2 = 1 0 0 = > x + 2 x − 1 + 2 ∗ ( x + 2 x − 1 ) ( x − 2 x − 1 ) + x − 2 x − 1 = 1 0 0 = > 2 x + 2 ∗ x 2 − ( 2 x − 1 ) 2 = 1 0 0 = > 2 x + x 2 − 2 x + 1 = 1 0 0 = > 2 x + 2 ∗ ( x − 1 ) = 1 0 0 = > 2 x + 2 x − 2 = 1 0 0 = > 4 x = 1 0 2 = > x = 4 1 0 2 = 2 5 1 Therefore,a=51,b=2 a+b=53
square both sides to get ( x + 2 x − 1 ) + 2 ( x + 2 x − 1 ) ( x − s q r t 2 x − 1 ) + ( x − 2 x − 1 ) = 1 0 0 the first and third terms can be added for simplification, and the second term can also be simplified using difference of two squares. the result is this: 2 x + 2 x 2 − 2 x + 1 = 1 0 0 the second term involves the square root of a perfect square, so it becomes: 4 x − 2 = 1 0 0 this is easily solved as: x = 2 5 1 so the solution is 5 1 + 2 = 5 3
lets (2x-1)=t^2 so we have x= (t^2+1)/2 => sqrt(t^2+1+2t)/2 + sqrt(t^2+1-2t)/2 = 10 => solving the Bracket => t+1 + t-1 = 10sqrt2 => t=5sqrt2 => t^2 = 50 => x = 51/2 = a/b so a+b= 53 :D
squaring on both side we get
x+√2x+1 +x-√2x-1 +2√(x-1)2 =100
2x+2(x-1)=100
x+x-1=50
2x=51
x=51/2
where a=51 and b=2
so a+b= 51+2=53
First off, we shift over one of the square roots.
x + 2 x − 1 = 1 0 − x − 2 x − 1
Squaring each side, we arrive at:
x + 2 x − 1 = 1 0 0 − 2 0 x − 2 x − 1 + x − 2 x − 1
Continuing,
2 0 x − 2 x − 1 = 1 0 0 − 2 2 x − 1 1 0 x − 2 x − 1 = 5 0 − 2 x − 1
Square again,
1 0 0 x − 1 0 0 2 x − 1 = 2 5 0 0 − 1 0 0 2 x − 1 + 2 x − 1
1 0 0 x = 2 5 0 0 + 2 x − 1
9 8 x = 2 4 9 9
x = 9 8 2 4 9 9 = 2 5 1
Thus a + b = 5 1 + 2 = 5 3
x + 2 x − 1 + x − 2 x − 1 = 1 0 → Square both sides, we get x + 2 x − 1 + x − 2 x − 1 + 2 ( x + 2 x − 1 ) ( x − 2 x − 1 ) = 1 0 0 ⇔ 2 x + 2 x 2 − 2 x + 1 = 1 0 0 ⇔ 2 x + 2 ( x − 1 2 ) = 1 0 0 ⇔ 2 x + 2 ( x − 1 ) = 1 0 0 ⇔ 4 x = 1 0 2 ⇔ x = 4 1 0 2 = 2 5 1 So, a + b = 5 1 + 2 = 5 3
√(x+√(2x-1)) +√(x-√(2x-1)) = 10
〖(√(x+√(2x-1)) +√(x-√(2x-1)) )〗^2= 〖10〗^2
x + √(2x-1) + 2.√((x+√(2x-1)).(x-√(2x-1)) ) + x - √(2x-1) = 100
2x + 2(√(x^2-2x+1)) = 100
2x + 2(x-1) = 100
x + x-1 = 50
2x = 51
x = 51/2
a = 51, b = 2
a+b = 51 + 2 = 53
Squaring both sides of the equation gives
2x + 2root(x^2-2x+1)=100
2x+2(x-1)=100
4x=102
x=51/2
Therefore 51+2 =53
wrong
Squaring both sides we get x + 2 x − 1 + x − 2 x − 1 + 2 ( x + 2 x − 1 ) ( x − 2 x − 1 ) = 1 0 2 2 x + 2 x 2 − 2 x + 1 = 1 0 0 ⇒ 2 x + 2 ( x − 1 ) = 1 0 0 ⇒ 4 x = 1 0 2 ⇒ x = 2 5 1 ⇒ a + b = 5 3
Let (2x-1)^1/2=y =>2x-1=y^2; by putting y in the given equation... (x+y)^1/2 + (x-y)^1/2 =10 taking both side square, 2x+2*(x^2-y^2)^1/2=100; by putting value of y^2=2x-1 in the equation 2x+2(x-1)=100; =>x=51/2=a/b; a+b=53 sol.
Pretty simple algebra, anybody who knows how to square and knows the factors of two perfect squares can do this easily
It may be pretty simple algebra, but you must know your facts well!
For example, ( 0 − 1 ) 2 = 0 − 1 .
If we square the entire expression, we get 2 x + 2 x 2 − 2 x + 1 = 2 x + 2 ( x − 1 ) 2 = 1 0 0 , from which the answer immediately follows.
Let $ a=\sqrt{x+\sqrt{2x-1}} , b=\sqrt{x-\sqrt{2x-1}} $ We have: $m+n=10$ $mn=|x-1|$ $m^2 + n^2 =2x$ So, $2x+2|x-1|= (m+n)^2 = 10^2 =100$ So, $x=\frac{51}{2} So, a+b=53
Square both sides to get:
2 x + 2 x 2 − 2 x + 1 = 1 0 0
2 x + 2 ( x − 1 ) = 1 0 0
4 x = 1 0 2
Thus, x = 5 1 / 2 , so our answer is 53
sqrt( x + sqrt(2x - 1) ) + sqrt( x - sqrt(2x - 1) ) = 10
sqrt( x + sqrt(2x - 1) ) = 10 - sqrt( x - sqrt(2x - 1) ) "by squaring both sides"
x + sqrt(2x -1) = 100 - 20*sqrt( x - sqrt(2x - 1) ) + x - sqrt(2x -1)
2 sqrt(2x -1) = 100 - 20 sqrt( x - sqrt(2x - 1) )
sqrt(2x -1) = 50 - 10*sqrt( x - sqrt(2x - 1) )
> 10*sqrt( x - sqrt(2x - 1) ) = 50 - sqrt(2x -1) "by squaring both sides"
100 ( x - sqrt(2x - 1) ) = 2500 - 100 sqrt(2x - 1) + 2x - 1
100x - 100 sqrt(2x - 1) = 2500 - 100 sqrt(2x - 1) + 2x - 1
> 98x = 2499
>>>> x = 2499/98 = 51/2 = a/b
then a+b = 53
( x + 2 x − 1 + x + 2 x − 1 ) 2 = 4 x − 2 = 1 0 0
x = 5 1 / 2
Answer is 51 + 2 = 53
Square both sides, and simplify,then we get the following expression: 2(x^2-(2x-1))^0.5 + 2x = 100, then (x-1) + x = 50, So x=51/2 = a/b. So a+b = 53
Problem Loading...
Note Loading...
Set Loading...
Square both sides to get $$x + 2\sqrt{\left(x + \sqrt{2x - 1}\right)\left(x - \sqrt{2x - 1}\right)} + x = 100$$ $$2x + 2\sqrt{x^2 - 2x + 1} = 100$$ $$x + \sqrt{(x - 1)^2} = 50$$ $$x + |x - 1| = 50$$ If x − 1 ≤ 0 , then we get 1 = 5 0 , so no solution.
If x − 1 ≥ 0 , then we get $$x = \frac{51}{2}$$ Hence $$a + b = 51 + 2 = \boxed{53}$$
This is basically second problem from IMO 1959.